2023
DOI: 10.1093/mnras/stad3092
|View full text |Cite
|
Sign up to set email alerts
|

A polarization study of jets interacting with turbulent magnetic fields

Moun Meenakshi,
Dipanjan Mukherjee,
Gianluigi Bodo
et al.

Abstract: We investigate the effect of the jet’s immediate surroundings on the non-thermal synchrotron emission and its polarization properties. The ambient medium is equipped with a turbulent magnetic field, which is compressed and amplified by the jets as they progress. This leads to high polarization at the forward shock surface. The randomness in the magnetic polarities of the external fields in the shocked ambient medium (SAM) results in vector cancellation of the polarized components from the jet, thereby causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 118 publications
1
0
0
Order By: Relevance
“…In the active lobes, the overall behavior of magnetic field lines has been observed to align with the jet flow or the lobe edges (Hogbom, 1979;Black et al, 1992;Johnson et al, 1995), exhibiting a typical pattern commonly found in FR II radio sources (Bridle et al, 1994). This is consistent with a model wherein shock compression, arising from the interaction between the jet and ambient medium, plays a pivotal role in aligning the magnetic field longitudinally as shown by Laing (1981) (see also the recent numerical works by Giri et al, 2022a;Meenakshi et al, 2023). In this model, the jet material interacts with an ambient medium (plows into it) containing tangled fields, and the ensuing compression at the bow shock and shear at the boundary layer between the jet cocoon and the shocked ambient medium organizes the field along the lobe.…”
Section: Polarization Propertiessupporting
confidence: 72%
“…In the active lobes, the overall behavior of magnetic field lines has been observed to align with the jet flow or the lobe edges (Hogbom, 1979;Black et al, 1992;Johnson et al, 1995), exhibiting a typical pattern commonly found in FR II radio sources (Bridle et al, 1994). This is consistent with a model wherein shock compression, arising from the interaction between the jet and ambient medium, plays a pivotal role in aligning the magnetic field longitudinally as shown by Laing (1981) (see also the recent numerical works by Giri et al, 2022a;Meenakshi et al, 2023). In this model, the jet material interacts with an ambient medium (plows into it) containing tangled fields, and the ensuing compression at the bow shock and shear at the boundary layer between the jet cocoon and the shocked ambient medium organizes the field along the lobe.…”
Section: Polarization Propertiessupporting
confidence: 72%